Adaptive resource-saving technologies in agriculture: The role of biotechnologies and their impact on environmental safety - Adymkhanov Lema; Makarov Sergey; Belousov Ivan (BIO Web of Conferences)
The article examines the role of biotechnologies in agriculture and their impact on environmental safety. In the face of a growing population and changing climate conditions, it is important to develop adaptive technologies that promote resource conservation and reduce negative environmental impacts. Biotechnologies represent a powerful tool for creating such innovative solutions in agriculture. The article discusses various aspects of biotechnology application in agriculture, including increasing crop productivity, protecting plants from diseases and pests, and improving soil quality. Special attention is paid to environmental safety issues and comparative analysis of the impact of biotechnologies on the environment compared to traditional agricultural methods.